The variety and its meaning in the increasing of crop capacity - В. В. Шелепов; В. І. Іщенко; М. П. Чебаков; Г. Д. Лебедєва (Plant Varieties Studying and Protection, 2006)
Some examples concerning the meaning of notion "variety" and its role in the increasing of wheat productivity are covered in this article, Some historical aspects of the origin of this term and its use in the select ional work are given. At the example of varieties